REPRESENTASI NILAI-NILAI LOKAL KAMPUNG ADAT MAHMUD DAN DESA CINTA DAMAI DALAM PRODUK KRIYA - Dede Ananta; Azis Nurkholis Majid; Hanni Haerani (LPPM Politeknik Pajajaran ICB, 2025)
Local wisdom is a string of Pearls that forms the identity of a region, so it must be maintained and preserved so that it does not become extinct. A strong culture is also a guideline for people in living their daily lives, which reflects the noble values that shape the character of a region. This research aims to identify and analyze the representation of local values in the research team's craft products inspired by the local wisdom of the Mahmud traditional village in Bandung Regency, West Java, and Cinta Damai Village in Samosir, North Sumatra. This activity is a collaboration between LPPM ISBI Bandung and UHN North Sumatra to increase tourism in the area. This research uses an analytical descriptive method that deeply examines how cultural values, traditions, and local wisdom from the two regions can manifest into the forms and motifs of the resulting craft products. The results of this research are expected to provide a better understanding of the richness of Indonesian culture, especially in the context of crafts, and be an educational resource for the community about the importance of preserving and developing local culture. This research is also expected to contribute to creating a sustainable craft industry while still paying attention to cultural values that are full of meaning.